2011
DOI: 10.5402/2011/384825
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trapping Method on Leukocyte Profiles of Black-Chested Spiny-Tailed Iguanas (Ctenosaura melanosterna): Implications for Zoologists in the Field

Abstract: When wild animals are captured for zoological research, researchers must choose a method of capture, and often this can be some form of passive, baited cage trap, or a direct capture with nets or nooses. If information on basal levels of circulating leukocytes is a goal, these two methods may provide different information, since recent evidence indicates that animals that enter cage traps experience stress, and, elevated stress hormones are known to alter leukocyte numbers in circulation by lowering lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The effects of APAP overdose on reptilian WBC have not been investigated, but in mammals APAP induces apoptosis of peripheral blood lymphocytes 17 . It is well established that elevations in stress hormones also decrease the number of circulating lymphocytes across all vertebrate taxa 18,19 . However, increases in corticosteroid levels also increase the numbers of circulating heterophils 18,19 , and snakes in the APAP group sampled 12 h post-dose presented heterophil counts no different than those of the controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of APAP overdose on reptilian WBC have not been investigated, but in mammals APAP induces apoptosis of peripheral blood lymphocytes 17 . It is well established that elevations in stress hormones also decrease the number of circulating lymphocytes across all vertebrate taxa 18,19 . However, increases in corticosteroid levels also increase the numbers of circulating heterophils 18,19 , and snakes in the APAP group sampled 12 h post-dose presented heterophil counts no different than those of the controls.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that elevations in stress hormones also decrease the number of circulating lymphocytes across all vertebrate taxa 18,19 . However, increases in corticosteroid levels also increase the numbers of circulating heterophils 18,19 , and snakes in the APAP group sampled 12 h post-dose presented heterophil counts no different than those of the controls. Thus, the cause of the observed decrease in number in circulating lymphocytes, while implicating apoptosis, is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Eshar et al [ 61 ] found that heterophils were the most abundant leukocytes type in wild common chameleons. As part of their study of leukocyte profiles of an iguanid species, Davis et al [ 62 ] reviewed several studies of white blood cell profiles of iguanids and other lizard species. They extracted data on the relative numbers of all cell types (mean percentages) and categorized the studies based on whether lizards were from captivity or the wild.…”
Section: Discussionmentioning
confidence: 99%
“…All animals were captured on the island of Cayo Cochino Menor (Little Hog Island) in the Cayos Cochinos archipelago off the Atlantic coast of Honduras, as a part of a larger capture mark recapture (CMR) project to understand the population ecology of this critically endangered species [ 9 ]. Cayo Cochino Menor has an area of approximately 65 hectares and is 1.5 kilometers from north to south and 1.1 kilometers from east to west with a highest elevation point of 140 m. For additional details of the study site see Davis et al [ 10 ]. Iguanas were captured with either baited wire mesh traps or by noose [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cayo Cochino Menor has an area of approximately 65 hectares and is 1.5 kilometers from north to south and 1.1 kilometers from east to west with a highest elevation point of 140 m. For additional details of the study site see Davis et al [ 10 ]. Iguanas were captured with either baited wire mesh traps or by noose [ 10 ]. Upon capture we determined the gender of each iguana (if possible) and measured its snout-vent length (in cm), which served as an index of body size.…”
Section: Methodsmentioning
confidence: 99%